PENGARUH PERILAKU EMPAT PILAR GIZI SEIMBANG TERHADAP KEJADIAN HIPERTENSI PADA PASIEN RAWAT JALAN DI RSUD KOTA BIMA - Fahrani, Aiska; Alkhair, Alkhair; Darmin, Darmin; Zara Avila, Dea (Lafadz Jaya Publisher, 2026)
Hypertension is a noncommunicable disease with a steadily rising prevalence and is a major risk factor for cardiovascular disease. This study aims to analyze the effect of the four pillars of balanced nutrition on the incidence of hypertension among outpatients at the Bima City General Hospital. The study used a quantitative analytical approach with a case-control design. The study population consisted of 305 outpatients, with a sample of 78 respondents comprising 39 cases and 39 controls selected using purposive sampling. The research instruments consisted of a questionnaire on the four pillars of balanced nutrition and a blood pressure monitor. Data analysis used univariate and bivariate tests with the Chi-Square test and Odds Ratio at a significance level of 0.05. The results of the study indicate that a varied diet (p = 0.039), physical activity (p = 0.000), weight monitoring (p = 0.042), and the total score for the four pillars of balanced nutrition (p = 0.000) have a significant effect on the incidence of hypertension, while clean living behaviors did not have a significant effect (p = 0.481). The conclusion of this study is that the four pillars of balanced nutrition play an important role in controlling hypertension, particularly physical activity as the most dominant factor.